2017
DOI: 10.1111/xen.12299
|View full text |Cite
|
Sign up to set email alerts
|

D‐dimer level, in association with humoral responses, negatively correlates with survival of porcine islet grafts in non‐human primates with immunosuppression

Abstract: Intravascular coagulation, in association with immune responses against xenografts, may partly contribute to loss of islet grafts in NHPs after PITx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…They showed that the increase of TNF‐α in human blood after contact with porcine endothelial cells (PECs) contributed to the subsequent activation of complement and procoagulant changes in PEC with tissue factor expression, suggesting that the control of TNF‐α was critical for the control of xenoreactive immune responses. They demonstrated that the predictors or causative factors of graft loss could be the alternative pathway of complement activation, the level of the fibrin degradation product D‐dimer, and anti‐Gal IgM Ab in pig‐to‐NHP islet xenotransplantation and C3a in aqueous humor of the anterior chamber in the eye after cornea xenotransplantation. For cell‐mediated immune response monitoring, the enzyme‐linked immunospot (ELISPOT) analysis to assess the functional antigen‐specific T cells has been established …”
Section: Research Activities In Xenotransplantationmentioning
confidence: 99%
“…They showed that the increase of TNF‐α in human blood after contact with porcine endothelial cells (PECs) contributed to the subsequent activation of complement and procoagulant changes in PEC with tissue factor expression, suggesting that the control of TNF‐α was critical for the control of xenoreactive immune responses. They demonstrated that the predictors or causative factors of graft loss could be the alternative pathway of complement activation, the level of the fibrin degradation product D‐dimer, and anti‐Gal IgM Ab in pig‐to‐NHP islet xenotransplantation and C3a in aqueous humor of the anterior chamber in the eye after cornea xenotransplantation. For cell‐mediated immune response monitoring, the enzyme‐linked immunospot (ELISPOT) analysis to assess the functional antigen‐specific T cells has been established …”
Section: Research Activities In Xenotransplantationmentioning
confidence: 99%
“…Graft loss in NHPs after intraportal PITx is mediated by multiple mechanisms and pathways ranging from instant blood‐mediated inflammatory reactions to adaptive immune responses . The primary pathway that contributes to graft loss may differ depending on the biological context at a given time point . Despite recent progress in the development of multiple gene‐modified pigs, immune suppression (IS) therapy is inevitably required for long‐term success of islet xenografts .…”
Section: Introductionmentioning
confidence: 99%
“…GA is clinically utilized as a sensitive indicator of short‐term improvement in glycemic control and glycemic instability in patients with insulin‐dependent diabetes . We have previously demonstrated that the levels (%) of GA accurately reflect the state of blood glucose control in rhesus PITx recipients . To identify a supplemental method to monitor porcine islet graft function in NHP models, we investigated the utility of GA. We analyzed cohort blood samples collected from NHP recipients during our previous PITx experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Although a recent pre-clinical study by Shin et al showed long-term control of diabetes in NHPs by the transplantation of wild-type adult porcine islets [44], a study by Kang et al showed that higher D-dimer levels negatively correlated with survival of porcine islet xenografts [45]. Despite more data becoming available on pig islet xenotransplantation in NHPs, the streptozotocin-induced diabetes model in NHP is still under debate [46].…”
Section: Introductionmentioning
confidence: 99%